Angiotensin II receptor type 1 gene expression in human glomerulonephritis and diabetes mellitus - Wagner, Jürgen; Gehlen, Frank; Ciechanowicz, Andrzej; Ritz, Eberhard (Journal of the American Society of Nephrology, 1999)
The renin-angiotensin system plays an important role in the progression of chronic renal disease. Although the expression of renin and angiotensin-converting enzyme in experimental and human renal disease has been well characterized, no information is available regarding human angiotensin type 1 (AT1) receptor expression. The net effect of renin depends on AT1 receptor expression, among other factors. Receptor expression was determined in renal biopsy samples (including all tissue components) and isolated glomeruli from patients with glomerulonephritis (GN) or diabetic nephropathy (non-insulin-dependent diabetes mellitus). Biopsy samples and isolated glomeruli from tumor-free tissue from tumor nephrectomies served as controls. Human AT1 receptor gene expression was determined by quantitative reverse transcription-PCR, using an AT1 receptor deletion mutant as the internal standard. In whole biopsy samples from 37 patients with various types of GN, AT1 receptor mRNA levels were lower, compared with nine control biopsy samples (P < 0.001). AT1 receptor mRNA levels were also significantly lower (P < 0.001) in eight samples from patients with diabetic nephropathy. In microdissected glomeruli, AT1 receptor gene expression was significantly lower in samples from patients (n = 22) with various types of GN, compared with 12 microdissected tumor nephrectomy control samples (P < 0.0023). It is concluded that AT1 receptor mRNA expression is low in glomeruli of patients with chronic renal disease. This may reflect a regulatory response to (inappropriately) high intrarenal angiotensin II concentrations.
Gesehen am 14.10.2021